Andisols from Tondano Area, North Sulawesi: Properties and Classification - Hikmatullah, . (JOURNAL OF TROPICAL SOILS, 2008)
Three pedons of Andisol (TN-1, TN-2 and TN-3) developed from young volcanic materials of the Lokon, Soputan, and Lengkoan volcanoes respectively in the Tondano area, North Sulawesi, were studied in the field, and 18 soil samples were analysed in the laboratory for physical, chemical, and mineralogical properties, and they were classified according to Keys to Soil Taxonomy 2003. The results indicated that all the pedons meet the requirements of the andic soil properties, and thus classified into Andisol order. Pedon TN-1 meets bulk density < 0.90 g cm-3, P retention > 85%, and (Alo + 0.5Feo) content extracted by ammonium oxalate > 2.0%, while pedons TN-2 and TN-3 meet the requirements of P retention > 25%, (Alo + 0.5Feo) content > 0.4%, volcanic glass content > 5%, and value of [%(Alo+0.5Feo) x 15.625 + (% volcanic glass)] is > 36.25. Composition of sand mineral fraction indicate that pedon TN-1 and TN-3 show andesitic to basaltic volcanic materials, whereas pedon TN-2 with high olivin content belongs to basaltic volcanic materials. Clay minerals of all the pedons was dominated by hydrated-halloysite with few of disordered-kaolinite, which indicated a little weathering of the pedons. The pedons were classified at family level as Typic Hapludand, medial, amorphic, isothermic (TN-1), Humic Udivitrand, ashy, amorphic, isothermic (TN-2), and Alfic Hapludand, medial, glassy, isothermic (TN-3).